Класифікація лексем прозових творів Гната Хоткевича як основа вивчення його ідіостилю - Подолянчук, О. (Філологічний дискурс, 2018)
У статті подано класифікацію лексем прозових творів Гната
Хоткевича як основу вивчення його ідіостилю, зокрема
проаналізовано твори та згруповано лексеми у певні тематичні
групи, що дасть змогу в подальшому визначити індивідуальний стиль
письменника. The article provides a classification of tokens prose of Hnat Khotkevych as the
basis of his study of diastole, in particular the analysis of such works as «The
Materials about the Customs, Life of Hutsuls (Records, Notes, Excerpts of Works)»;
play «Railroad»; story «Life on the Mountain» from the book «Mountain Watercolor»,
«Fornication», «For Yurishtanom», «Magic Stick», «Dovbusha Offspring» (excerpts)
fragments of stories «Flows from the Mountains», «Unfinished Presbytery», «People»,
«Gelles around the Corner»; Hutsul stories of life; drama «The Sea», «People People»
and «I Love Women»; story «Had Seen the Rock» and excerpts of literary works,
which names have not been established («Hermit», «Joy», «Grandfather Andrew»,
«Triumph of Music», Everything Goes ... Everything Passes», «From Studies in
Crowd», «Bella Donna»,»The Last Lecture», etc.). Tokens are grouped in certain
thematic groups that will help further define the individual style of the writer:
nominated to refer individuals for family ties and affinity, nominated to describe
clothing, outbuildings, residential buildings, business things, names of dishes,
struggle against oppression and injustice, fishing, product processing and
professions by the type of activity, dialects, extent of natural objects and landscapes
artificial, etc. They are considered as a means of expressiveness of language
characters where the work reflects certain lexical structures. It is determined that
the tokens used by Hnat Khotkevych in his works, is a valuable component, its
unsurpassed diastole. They are characterized by a rich multiplicity of Hutsul color.